Thermodynamic, Electromagnetic, and Lattice Properties of Antiperovskite Mn3SbN. (10th January 2013) - Sun, Ying; Guo, Yan-Feng; Tsujimoto, Yoshihiro; Wang, Xia; Li, Jun; Sathish, Clastin I.; Wang, Cong; Yamaura, Kazunari
Abstract : The physical properties of polycrystalline Mn3 SbN were investigated using measurements of the magnetic, calorimetric, and electronic transport properties. At room temperature, the phase crystallizes in a tetragonal structure with P 4 / m m m symmetry. A remarkably sharp peak in the heat capacity versus temperature curve was found near 353 K. The peak reaches 723 J mol −1  K −1 at its highest, which corresponds to a transition entropy of 10.2 J mol −1  K −1 . The majority of the large entropy change appears to be due to lattice distortion from the high-temperature cubic structure to the room-temperature tetragonal structure and the accompanying Ferrimagnetic transition.